A Constructive Theology of Art How the 27th National Tarjih Congress Decision Reads the Qur'an and Hadith - Agus Purwanto; Triyo Supriyatno; Zulfi Mubaraq (Institut Agama Islam Negeri (IAIN) Curup, 2026)
Muhammadiyah, a modernist Islamic movement in Indonesia, is often narrowly understood in both academic and public discourse as rejecting art. However, its official decisions actually build a positive theological foundation for art. This study examines how the 27th National Tarjih Congress Decision on Guidance for Islamic Art and Culture employs the Qur'an and ḥadīth to construct a constructive theology of art. Using a library-based qualitative approach with content analysis of the Tarjih document and al-Fārūqī's tawḥīdic aesthetics as a framework, this research finds that the decision constructs such a theology through five pillars: fiṭrah; reinterpretation of ḥadīths via 'illat al-ḥukm; Sufi values through iḥsān; a cultural strategy balancing purification and accommodation; and Al-Mā'ūn's social concern—challenging the narrow view of Muhammadiyah as anti-art. The decision thus formulates a theology of art that not only permits art legally but also positions it as part of Muslims' spiritual and social mission. This research offers a new reading of an official Muhammadiyah document and a theoretical framework for analyzing theology of art in contemporary Islam.